A new virtual reality tool for unilateral cerebral palsy rehabilitation: Two single-case studies. (December 2013) - Dinomais, Mickaël; Veaux, Fabienne; Yamaguchi, Takehiko; Richard, Paul; Richard, Isabelle; Nguyen, Sylvie
Abstract Objective: To examine the "clinical utility" of a new virtual rehabilitation tool in order to treat upper-limb motor deficit in cerebral palsy (CP) patient. Methods: Single-case experimental designs. Virtual reality intervention was performed in two left unilateral spastic CP adolescent patients. The virtual reality intervention was given for 60 minutes per session, two sessions a day, and 5 days a week over 2 weeks. Results: For each patient and for both hands, the number of blocks transported within one minute (box and block test scores) is increased. The nonoverlap of all pairs indices for the paretic hand were calculated as 0.95 for subject 1 and 0.93 for subject 2, and the nonoverlap of all pairs indices for the nonparetic hand were calculated, respectively, as 0.92 and 1. Conclusion: We provide empirical evidence in support of a new simple Virtual Rehabilitation system in CP patient to improve upper-limb motor function.